Nutrient limitation in Clostridium autoethanogenum and characterisation of its carbonic anhydrase - Pander, Bart (2018)
Clostridium autoethanogenum is an anaerobic, facultative autotrophic bacterium that was isolated from rabbit faces in the last decennium of the twentieth century. It is used to convert carbon monoxide rich waste gas in to compounds such as acetate, ethanol, 2,3-butanediol and lactate. Carbon dioxide reacts with water to form carbonic acid and bicarbonate. This reaction is catalysed by enzymes called carbonic anhydrases. It was unknown if these enzymes were present in C. autoethanogenum. Genes encoding putative carbonic anhydrases were cloned and heterologous expressed. One gene encoded an active enzyme of a novel sub-clade of β-carbonic anhydrases. This gene was disrupted in the genome of C. autoethanogenum. The mutant was unable to grow at low pH and low carbon dioxide concentrations. Production of ethanol and 2,3-butanediol by WT C. autoethanogenum in carbon monoxide fed chemostat cultures was improved by employing phosphate limitation. A pilot study on the effect of phosphate limitation on rhamnose based growth showed 1,2-propanol and 1-propanol as native products of C. autoethanogenum. Acetolactate is the metabolic branch point for both branched chain amino acid and 2,3-butanediol production. An acetolactate synthase gene was deleted. The resulting mutant shows a subtle growth difference in media containing amino acids. Finally the strength of a series of heterologous promoters was determined in C. autoethanogenum. The research presented in this thesis improves our knowledge on C. autoethanogenum’s metabolism and offers tools to optimise it for product formation. This will enable improved exploitation of this organism for a carbon neutral future.